The Association between Energy and Protein Density with Obesity among Adults in Tembokrejo Sub-District, Pasuruan City - Adistyrianti, Ludya Cahyani; Jannah, Miftahul; Amareta, Dahlia Indah; Elisanti, Alinea Dwi (Journal of Public Health for Tropical and Coastal Region, 2025)
Introduction: Adult obesity is a major nutritional concern, with a national prevalence of 21.8% and 22.4% in East Java Province and 19.9% in Pasuruan City, respectively. Consumption of energy- and protein-dense foods, combined with low physical activity and urban lifestyle patterns, were the main contributing factors. This study aimed to examine the association between energy density, protein density, and obesity among adults in the Tembokrejo Sub-District of Pasuruan City.Methods: This was an analytical observational study with a cross-sectional design involving 192 adult respondents selected through simple random sampling. The researchers and enumerators visited one of the residents houses, where several respondents were located within the same neighborhood unit. Energy and protein density were assessed using the 2 days of 24-h food recall method, while obesity was determined based on Body Mass Index (BMI) calculated from measured height and weight. Data analysis was conducted using the chi-square test.Results: There were 68.2% of women respondents in the study. About a third were aged 19.29 years, 30-50 years and > 50 years, respectively. Individuals consuming high-energy-dense foods were 14 times more likely to develop obesity (p=0.000), whereas those consuming high-protein-dense foods are 2 times more likely to develop obesity (p=0.001).Conclusion: Energy and protein densed food consumptions associated with obesity among adults in Tembokrejo Sub-District, Pasuruan City. It is recommended that the community regulates the consumption of high-energy and protein-dense foods as a preventive measure against obesity.